Test Simulation using Finite Element Method - Ali, Mohd Basri (IOP Publishing/International, the Conference on Advanced Materials and Nanotechnology (CAMAN 2009) held on 3–5 November 2009 in Putra World Trade Centre (PWTC), Kuala Lumpur, Malaysia., 2011)
The dynamic responses of the standard Charpy impact machine are experimentally studied using the relevant data acquisition system, for the purpose of obtaining the impact response. For this reason, the numerical analysis by means of the finite element method has been used for experiment findings. Modelling of the charpy test was performed in order to obtain strain in the striker during the test. Two types of standard charpy specimens fabricated from different materials, i.e. aluminium 6061 and low carbon steel 1050, were used for the impact simulation testing. The related parameters on between different materials, energy absorbed, strain signal, power spectrum density (PSD) and the relationship between those parameters was finally correlated and discussed.